Space & event in contested territories: Public assembly through place-making tradition exploring tectonics and materials of the circular economy - Nunkoo, Abhinav (School of Architecture, Planning and Geomatics, 2018)
Design is an iterative process. This design dissertation explores 'concept-form' by Tschumi (2010, pp. 15-19) who argues it is a generator of new conditions to freely inform or locate activities to generate events. Concept-form reflects a specific moment in a thought process when an architectural strategy becomes the generator for making buildings, Concept-form is about designing conditions rather than conditioning designs. The research by design dissertation report contains sketches, parti diagrams, and artworks as social, contextual and technical constraints are super-imposed as we move across scales towards a concluding architectural intervention addressing Space & Event in the context of contested territories in Cape Town.